Rehabilitasi Sarana Prasarana di MTSN 2 Sidoarjo - Fauziyah, Ni'matul; Rosyid , Moch. Iqbal Rizki; Afifah, Faiqotul (LPPM Universitas Bina Bangsa, 2024)
Facilities and infrastructure are important components or resources in the realm of education because they are related to learning activities. So it is necessary to have management of facilities and infrastructure that are organized to support the success of teaching and learning itself. Management of facilities and infrastructure includes planning, procurement, inventory, maintenance, disposal and rehabilitation of educational facilities and infrastructure. The discussion of rehabilitation is interesting in this study, because rehabilitation is a determining factor in how capable an educational institution is to run it. Therefore, the researcher is interested in conducting research related to rehabilitation at MTsN 2 Sidoarjo and seeing how competent the components in the madrasah are in managing its facilities and infrastructure, this is the purpose of the research conducted by the researcher. The research method in this study uses a qualitative method. The resource person in this study is Mrs. Mia Evyanti, M.Ed., as the Deputy Head of Facilities and Infrastructure. Data collection techniques are carried out through observation, interviews and documentation. The results of the research in this article show that the components in the madrasah have managed facilities and infrastructure in terms of rehabilitation very well, as evidenced by the analysis of rehabilitation financing and grouping in the implementation of long-term and short-term rehabilitation in the madrasah